New Species and Records of Costa Rican Featherwing Beetles (Coleoptera:Ptiliidae) - Darby, Michael (Zootaxa, 2016)
This paper describes a new genus and species of Acrotrichinae, Seminis factiosum gen. n., sp. n.; two new species of Nossidium: Nossidium schuelkei, n. sp. and Nossidium issyae, sp. n.; and  a new species of Ptenidium (Peruvium), Ptenidium gruenbergae  sp. n. from Costa Rica. Three further species: Ptenidium nitidum (Heer),  Petrotrichis rotundata Darby, and Bambara invisibilis Nietner are recorded as being present. With the exception of N. issyae all the insects were collected using a vehicle roof–mounted net on a single 40  kilometre drive from the east and west coasts of the Osa Peninsula by M. Schülke and B. Grünberg in 2012.